Step * 1 1 of Lemma eu-exists-middle


1. EuclideanStructure@i'
2. [%1] euclidean-axioms(e)@i'
3. Point@i
4. Point@i
5. {p:Point| ¬Colinear(a;b;p)} @i
⊢ (middle(a;b;c) middle(a;b;c) ∈ Point) ∧ amiddle(a;b;c)=bmiddle(a;b;c) ∧ amiddle(a;b;c)=cmiddle(a;b;c)
BY
(Unhide THENA Auto) }

1
1. EuclideanStructure@i'
2. euclidean-axioms(e)@i'
3. Point@i
4. Point@i
5. {p:Point| ¬Colinear(a;b;p)} @i
⊢ (middle(a;b;c) middle(a;b;c) ∈ Point) ∧ amiddle(a;b;c)=bmiddle(a;b;c) ∧ amiddle(a;b;c)=cmiddle(a;b;c)


Latex:


Latex:

1.  e  :  EuclideanStructure@i'
2.  [\%1]  :  euclidean-axioms(e)@i'
3.  a  :  Point@i
4.  b  :  Point@i
5.  c  :  \{p:Point|  \mneg{}Colinear(a;b;p)\}  @i
\mvdash{}  (middle(a;b;c)  =  middle(a;b;c))  \mwedge{}  amiddle(a;b;c)=bmiddle(a;b;c)  \mwedge{}  amiddle(a;b;c)=cmiddle(a;b;c)


By


Latex:
(Unhide  THENA  Auto)




Home Index